Pathogenic bacteria in turkey meat: A review - Silva, Higor Oliveira [UNESP]; Centola Vidal, Ana Maria; Rossi Junior, Oswaldo Durival [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2017)
Besides the advances in the adoption of programs regarding food safety and control, the surveillances system still have been reporting the occurrence of foodborne diseases (FBD) in developed and developing countries, and turkey meat is often involved in outbreaks affecting a large amount of human beings annually. Bacteria are responsible by more than 66% of cases of FBD resulting in hospitalizations and highlighting the importance of Salmonella spp., Campylobacter sp., Escherichia coli, Listeria monocytogenes, Staphylococcus spp., Clostridium botulinum and Clostridium perfringens. The contamination sources of turkey carcasses are similar to poultry, however; the reports regarding the involvement of turkey meat in FDB and its risk to public health is rare. Thus, this review focused on identify the microorganisms reported in turkey meat's outbreaks and their risk factors and mainly contamination sources, as well the limitations to study their epidemiology from farm to consumers. A high-risk was attributed to the genus Salmonella spp., Escherichia coli, Staphylococcus spp. and Campylobacter sp., and the latest is considered as neglected in developing countries. This study shown the need of a higher incentive to researches regarding the sanitary conditions of turkey meat processed in Brazil, as well as the need of monitoring this meat sold in the country.
Keywords: Salmonella spp.; Campylobacter sp.; Escherichia coli; Listeria monocytogenes; Staphylococcus spp.